Paysages Photographies : La Mission Photographique de la DATAR : travaux en cours 1984/1985. - Hers, François; Latarjet, Bernard; Mission Photographique de la DATAR (Paris : Editions Hazan, 1985)
Basilico, Gabriele ; Depardon, Raymond ; Despatin et Gobeli ; Doisneau, Robert ; Drahos, Tom ; Fastenaekens, Gilbert ; de Fenoyl, Pierre ; Garnell, Jean-Louis ; Giordan, Albert ; Hannappel, Werner ; Hers, François ; Lafont, Suzanne ; Milovanoff, Christian ; Ristelhueber, Sophie ; Trülzsch, Holger
Frans
boek